Pintong maraming silid (The door with many rooms) - Evasco, Eugene Y.; Ang, Leo Kemping; Villalon, Mixkaela (Quezon City LG & M, 2013)
"This book is a riddle. Discover the mystery in its cover and pages. Magic and sparkle await every turn of its page."
Donated by Eugene Y. Evasco.
Para sa edad/For ages 8-12.
Text in Filipino and English.
Keywords: Riddles, Philippines